ALAT PENGUKUR PEMAKAIAN ENERGI LISTRIK MENGGUNAKAN SENSOR OPTOCOUPLER DAN MIKROKONTROLER AT89S52 - Subito, Mery; -, Rizal (FORISTEK : Forum Teknik Elektro dan Teknologi Informasi, 2012)
Abstract - kWh-meter as an each hour electrical energy consumption measurer is still using conventional tools which only records the amount of electrical energy used in each hour. By using AT89S52 microcontroller and optocoupler sensor, the conventional kWh-meter was modified to be a measurer which is not only display s the amount of the used electrical energy but also shows the value of money in rupiahs that should be paid by the customer. The principle of how this system works is PLN as a power source of kWh-meter moves the disc of kWh-meter when it is in the underload condition. When the disc spin and pass the optocoupler sensor, the sensor will turn on. Each time the disc cuts the beam of light, the sensor will instruct the microcontroller, the main controller, to process the execution instruction. This execution instruction results in the reading of both a number of rounds per kWh and an amount of rupiahs display ed in LCD. Â Keywords : kWh-meter, microcontroller, optocoupler